Case report: Ibogaine reduced severe neuropathic pain associated with a case of brachial plexus nerve root avulsion - Dickinson, Jonathan E.; Inzunza, Jose Adalberto Dominguez; Perez-Villa, Liliana; Millar, Trevor G.; Pushparaj, Abhiram P. (Frontiers in Pain Research, 2023)
Brachial plexus nerve root avulsion results from complete separation of the nerve root from the spinal cord and is one of the most challenging types of neuropathic pain, coinciding with motor, sensory and autonomic deficits. The severe pain and typical impossibility of root reattachment often leads to requests for amputation. Ibogaine is an indole alkaloid producing psychoactive effects through reported actions upon multiple neurotransmitter systems, including NMDA, κ-and µ-opioid receptors and σ2 receptor sites, along with stimulation of neurotrophic factors GDNF and BDNF. In this case report we describe a 53-year-old male with two decades of severe intractable pain due to brachial plexus nerve root avulsion from vehicular trauma who was successfully treated with both high dose inpatient and low dose outpatient administrations of ibogaine. Though promising for future study, the adverse effects of high dose ibogaine administrations may limit tolerability of this saturation protocol to the most refractory cases.